Overall survival prediction in metastatic castration-resistant prostate cancer treated with radium-223 - Vidal, Monica (Int Braz J Urol, 2020)
OBJECTIVE: Radium-223(223Ra) is indicated for patients (p) with metastatic castration resistant prostate cancer (mCRCP). OBJECTIVES: The aim of this study was to evaluate the role of baseline clinical variables associated with overall survival (OS) and toxicity of 223Ra. Its purpose was to identify the factors that can predict a better response to treatment and provide information regarding the most appropriate time for the application of 223Ra. MATERIALS AND METHODS: Prospective study in 40p with mCRPC treated with 223Ra. End points were OS, progression-free survival and time to progression. The follow-up parameters were: doses received, hemoglobin (Hb), absolute neutrophil count (ANC), platelet count (PC), prostate specific antigen (PSA), alkaline phosphatase (ALP), Visual Analogue Scale for pain, Eastern Cooperative Oncology Group (ECOG) and WHO’s Cancer Pain Ladder. The use of other treatments was also evaluated. RESULTS: Median OS was 17.1 months(mo) (CI95%6.5-27.7); 26/40p received complete treatment of 223Ra, without reaching a median OS and 14p received incomplete treatment with a median OS 13.6mo(CI95%1.6-25.6). Median follow-up was 11.2mo (range:1.3-45.2). The univariate analysis showed that factors as VAS, ECOG, Hb and ALP values were independently associated with OS. First line treatment with 223Ra was started in 11/40p, while 19p had been heavily pre-treated and 13p received concomitant treatment. CONCLUSIONS: 223Ra therapy require an adequate selection of patients to obtain the greatest clinical benefit. Low basal Hb, hight basal ALP, bone marrow involvement and an altered ECOG were the main factors that decreased OS in our patients. 223Ra should be considered relatively early in the course of treatment.